Effects of residual disinfectants on the redox speciation of lead(ii)/(iv) minerals in drinking water distribution systems. Issue 2 (21st December 2020) - Avasarala, Sumant; Orta, John; Schaefer, Michael; Abernathy, Macon; Ying, Samantha; Liu, Haizhou
Abstract : This study investigated the reaction kinetics on the oxidative transformation of lead(ii ) minerals by free chlorine (HOCl) and free bromine (HOBr) in drinking water distribution systems. Abstract : This study investigated the reaction kinetics on the oxidative transformation of lead(ii ) minerals by free chlorine (HOCl) and free bromine (HOBr) in drinking water distribution systems. According to chemical equilibrium predictions, lead(ii ) carbonate minerals, cerussite PbCO3(s) and hydrocerussite Pb3 (CO3 )2 (OH)2(s), and lead(ii ) phosphate mineral, chloropyromorphite Pb5 (PO4 )3 Cl(s) are formed in drinking water distribution systems in the absence and presence of phosphate, respectively. X-ray absorption near edge spectroscopy (XANES) data showed that at pH 7 and a 10 mM alkalinity, the majority of cerussite and hydrocerussite was oxidized to lead(iv ) mineral PbO2(s) within 120 minutes of reaction with chlorine (3 : 1 Cl2  : Pb(ii ) molar ratio). In contrast, very little oxidation of chloropyromorphite occurred. Under similar conditions, oxidation of lead(ii ) carbonate and phosphate minerals by HOBr exhibited a reaction kinetics that was orders of magnitude faster than by HOCl. Their end oxidation products were identified as mainly plattnerite β-PbO2(s) and trace amounts of scrutinyite α-PbO2(s) based on X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS) spectroscopic analysis. A kinetic model was established based on the solid-phase experimental data. The model predicted that in real drinking water distribution systems, it takes 0.6–1.2 years to completely oxidize Pb(ii ) minerals in the surface layer of corrosion scales to PbO2(s) by HOCl without phosphate, but only 0.1–0.2 years in the presence of bromide (Br − ) due the catalytic effects of HOBr generation. The model also predicts that the addition of phosphate will significantly inhibit Pb(ii ) mineral oxidation by HOCl, but only be modestly effective in the presence of Br − . This study provides insightful understanding on the effect of residual disinfectant on the oxidation of lead corrosion scales and strategies to prevent lead release from drinking water distribution systems.